Hubungan Perilaku Dalam Mengkonsumsi Tablet Fe Terhadap Kejadian Anemia Pada Mahasiswi S1 Kebidanan Semester Lima Di Universitas 'Aisyiyah Yogyakarta: The Relationship Between Fe Tablets Consumption Behavior on The Incident of Anemia in Five Semester Midwifery Students at Universitas 'Aisyiyah Yogyakarta - Partiningsih, Surti; Fayakun Nur Rohmah (LPPM STIKES Guna Bangsa, 2025)
The increase in the prevalence rate of reproductive women who experience red blood cell deficiency reaches 29.9%, which is in line with the figure of more than half a billion reproductive women. Then the increase in the number of iron deficiency problems still exists in districts or cities in Yogyakarta with the incidence of anemia in 2019 and 2020 decreasing and then increasing again in 2021 with an anemia prevalence rate of 42%. According to this problem, the researcher wants to research the relationship between behavior in consuming Fe tablets and the incidence of anemia in fifth semester S1 Midwifery students at 'Aisyiyah University Yogyakarta. The purpose of this study is to determine the relationship between behavior in consuming Fe tablets and the incidence of anemia in S1 Midwifery students in the fifth semester at 'Aisyiyah University Yogyakarta. The type of research uses observational analysis with a cross sectional approach. The sampling technique used by the researcher in this study uses purposive random sampling with a total sample of 55 subjects. In this study, an ethical clearance test number 3271/KEP-UNISA/XI/2023 has been carried out. The instruments used in this study used a digital Hb check tool and a questionnaire sheet containing a set of written questions to the respondents. The results of the analysis of variables with chi square showed that there was a significant relationship between the behavior of consuming Fe tablets and the incidence of anemia by 0.009 (p<0.05).